Karakteristik Fluida Mata Air Panas Desa Kasuratan Kabupaten Minahasa menggunakan Spektroskopi Spektrofotometer dan FTIR - Omie Jawongkay; Donny Royke Wenas; Noldy Pulingkareng; Selfie Tumbel; Budi Mena; Cyrke Bujung (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
Indonesia has a geothermal energy potential of around 40 percent of the world's total geothermal energy, placing Indonesia as one of the countries rich in geothermal energy potential. North Sulawesi Province is one of the provinces in Indonesia that has geothermal potential. This research aims to determine the characteristics of hot spring fluids in Kasuratan Satu Village, Minahasa Regency using a spectrophotometer and FTIR. The method used is a geochemical method to study the characteristics of hot spring fluids and FTIR characterization. The results of the research show that the fluid characteristic of the hot spring manifestation in Kasuratan Satu Village is sulfate water (SO4), this is by FTIR measurements.